2020
DOI: 10.1021/acs.orglett.0c02427
|View full text |Cite
|
Sign up to set email alerts
|

NMR Quantification of Halogen-Bonding Ability To Evaluate Catalyst Activity

Abstract: Quantification of halogen-bonding abilities is described for a series of benzimidazolium-, imidazolium-and bis(imidazolium) halogen-bond donors (XBDs) using 31 P NMR spectroscopy. The measured Δδ( 31 P) values correlate with calculated activation free energy ΔG ‡ and catalytic activity for a Friedel−Crafts indole addition. This rapid method also serves as a sensitive indicator for Brønsted acid impurities.Letter pubs.acs.org/OrgLett

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
19
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 44 publications
3
19
0
Order By: Relevance
“…As we recently demonstrated that chlorinated solvents clearly interact in solution with Te σ‐holes, [12] we performed similar experiments with less competitive solvents than CDCl 3 , i. e. toluene‐ d8 and cyclohexane‐ d12 . In order to increase the strength of the Te⋅⋅⋅O interaction, a stronger σ‐hole acceptor (Et 3 PO [36] ) was also used. Under such conditions, NMR titration experiments could be performed, while titrations in CDCl 3 were not conclusive [37] .…”
Section: Resultsmentioning
confidence: 99%
“…As we recently demonstrated that chlorinated solvents clearly interact in solution with Te σ‐holes, [12] we performed similar experiments with less competitive solvents than CDCl 3 , i. e. toluene‐ d8 and cyclohexane‐ d12 . In order to increase the strength of the Te⋅⋅⋅O interaction, a stronger σ‐hole acceptor (Et 3 PO [36] ) was also used. Under such conditions, NMR titration experiments could be performed, while titrations in CDCl 3 were not conclusive [37] .…”
Section: Resultsmentioning
confidence: 99%
“…A review of the relevant literature data indicated that all of iododiazoliums (A-D) are known, but only C has been applied for XB-donating organocatalysis. [46][47][48][49][50] The diazoliums A and D served as precursors for the preparation of mesoionic carbene metal complexes by the Huynh [51][52][53][54] and Bera 55-57 groups, respectively. There is only one reported example of a type-B compound (i.e., 1,2-dimethyl-3-iodoindazoium iodide), and its potential applications have not yet been explored.…”
Section: Resultsmentioning
confidence: 99%
“…[65][66][67] LFERs between catalytic activity and halogen bonding association constants also have been observed. 46,68 Therefore, this phenomenon was the basis for the density functional theory (DFT) calculations carried out in this study to determine the activation energies of model reactions involving A*-N*. The hydrolysis of methyl chloride (TS1) and the coupling of ammonia and acetone (TS2) were chosen as simple model reactions (Scheme 1 and Table 1) because XB donors have typically been studied in reactions that either required elimination of a halogen atom or carbonyl activation.…”
Section: Density Functional Theory Calculationsmentioning
confidence: 99%
“…Fort hat, 17 Olabelled Ph 3 PO [21] was used as aprobe in NMR, expecting that direct 17 Oand 125 Te NMR monitoring of the interacting atoms would give key information on the interaction between the basic Ph 3 PO oxygen atom and the Te s-holes.U sing ap hosphine oxide as ChB acceptor could further allow 31 PNMR monitoring. [22] Once added to at elluronium dichloromethane-d 2 solution, Ph 3 PO induced significant shifts of the 17 O, 31 Pand 125 Te NMR signals (Table 1).…”
mentioning
confidence: 99%